PRO KONTRA STANDARISASI AKUNTANSI SYARIAH TERHADAP IFRS DI INDONESIA - Mariyam, Siti (Jurnal Akuntansi AKUNESA, 2014)
Economic development and islamic-based business thrives in Indonesia. This suggests that islamic accounting is a product of islamic economics is widely known in the community and the business community in Indonesia. Islamic economics itself appears in various countries that ideology Islam and Muslim population, including Indonesia. Islamic or sharia accounting accounting more emphasis on accountability, with an emphasis on truth and justice, which not only serve the shareholders as well as an emphasis on decision making alone, but also to all interested parties and comply with all laws are based on ethics and morality and the concept of justice and truth.Keyword: Islamic accounting, International Finance Reporting Standards, Justice.